Towards individualised treatment of urinary tract infections - Ellen V. Stadler; Alison Holmes; Danny O’Hare; Timothy M. Rawson (Communications Medicine)
Monitoring host- and pathogen-specific biomarkers alongside drug levels at the site of infection offers promise for personalised antimicrobial therapy. Here, we highlight the potential of longitudinally monitoring biomarkers in urine using existing technologies to enable individualised PK-PD optimisation in urinary tract infections.